PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL TERHADAP PEMAHAMAN SISWA KELAS V PADA MATERI DAUR AIR DI MI. ISTIQOMAH SEKAYU - Fatrisia, Marizka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using Wordwall-based interactive learning media on student understanding in the IPAS (Natural and Social Sciences) subject among fifth-grade students at MI Istiqomah Sekayu. The study employs a quantitative approach using a quasi-experimental design—specifically, a pretest-posttest control group design. The population consists of all fifth-grade classes at MI Istiqomah Sekayu, while the sample comprises only classes V.A and V.B. Data analysis involved normality tests, homogeneity tests, and hypothesis testing. The results indicate that the data are normally distributed and homogeneous. The hypothesis test yielded a Sig. (2-tailed) value of 0.000 (less than 0.05); consequently, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. This demonstrates a significant effect of using Wordwall-based interactive learning media on student understanding in the IPAS subject for fifth-grade students at MI Istiqomah Sekayu. This study is expected to serve as a reference for teachers in utilizing interactive learning media to enhance student understanding and create a more engaging and effective learning process.